Application of λ esophagojejunostomy in total gastrectomy under laparoscopy: a modified technique for post-gastrectomy reconstruction - Liu, Lang-Biao; Ruan, Guo-Tian; Wu, Ya-Dong; Niu, Lei; Cai, Jun (Frontiers in Oncology, 2024)
Objective Common gastrectomy methods can significantly affect patients’ postoperative quality of life. This study investigated the safety, feasibility, and short-term efficacy of λ-type esophagojejunostomy in total gastrectomy under total laparoscopy. Methods We retrospectively analyzed the clinical and follow-up data of 50 patients with adenocarcinoma of the gastric/gastroesophageal junction who underwent total laparoscopic radical gastrectomy with λ-type esophagojejunostomy at the Beijing Friendship Hospital from January 2021 to July 2022. Data are reported as mean ± standard deviation. Results Patients comprised 27 males and 23 females, aged 42 to 76 (60.9 ± 5.6) years. There were 26 cases of gastroesophageal junction adenocarcinoma (16 Siewert type II and 10 Siewert type III) and 24 cases of adenocarcinoma of the proximal gastric body. All patients underwent radical total gastrectomy and D2 lymph node dissection with λ-type esophagojejunostomy for digestive tract reconstruction under total laparoscopy. The total operation time was 235–295 (249.4 ± 48.5) min, digestive tract reconstruction time was (48.2 ± 23.2) min, intraoperative blood loss was (63.4 ± 48.4) mL, recovery time of exhaust was (3.1 ± 2.2) d, first drinking or eating time was (4.1 ± 2.1) d, and hospital stay was (9.3 ± 4.4) d. Three patients had postoperative complications, including one with duodenal remnant leakage combined with abdominal infection. Anastomotic bleeding and postoperative inflammatory intestinal obstruction occurred in one patient each, all of whom were cured by conservative treatment. The Nutritional Risk Index of the whole group was 53.5 ± 8.4 preoperatively, 47.3 ± 5.6 one week postoperatively, 50.3 ± 5.6 six months postoperatively, and 52.4 ± 4.2 at 12 months postoperatively. Roux-en-Y stasis syndrome and bile reflux esophagitis occurred in one patient each (2.0%). There were no occurrences of recanalization of the closed end of the afferent loop of the esophagojejunostomy anastomosis, anastomotic stricture or obstruction, or tumor recurrence. Conclusion λ-type esophagojejunostomy is safe and feasible for digestive tract reconstruction after total laparoscopic radical gastrectomy. This digestive tract reconstruction method not only maintains intestinal continuity but also simplifies surgical procedures, allowing patients to recover quickly with an excellent short-term effect.